2017
DOI: 10.1515/rrlm-2017-0028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-molecular weight alcohols on bacterial viability

Abstract: Alcohol based solutions are among the most convenient and wide spread aid in the prevention of nosocomial infections. The current study followed the efficacy of several types and isomers of alcohols on different bacterial species. Seven alcohols (ethyl, n-propyl, iso-propyl, n-butyl, iso-butyl, tert-butyl alcohol, and ethylene

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 21 publications
(17 reference statements)
1
17
0
Order By: Relevance
“…However, this high concentration of ethanol is toxic to most cells. We found that 15% ethylene glycol or 0.1% Tween-20 were effective and non-toxic agents ( Blank et al, 1987 ; Man et al, 2017 ) for re-wetting Nafion microcosms already inoculated with bacteria or fungi. For our experiments, we therefore slowly percolated 15% ethylene glycol into the microfluidics device using a syringe pump (3 µL total volume, 0.5 µL/min) to rehydrate the hydrophobic Nafion, followed by washing with MSN medium to remove ethylene glycol (20 µL total volume, 0.5 µL/min).…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…However, this high concentration of ethanol is toxic to most cells. We found that 15% ethylene glycol or 0.1% Tween-20 were effective and non-toxic agents ( Blank et al, 1987 ; Man et al, 2017 ) for re-wetting Nafion microcosms already inoculated with bacteria or fungi. For our experiments, we therefore slowly percolated 15% ethylene glycol into the microfluidics device using a syringe pump (3 µL total volume, 0.5 µL/min) to rehydrate the hydrophobic Nafion, followed by washing with MSN medium to remove ethylene glycol (20 µL total volume, 0.5 µL/min).…”
Section: Methodsmentioning
confidence: 95%
“…This makes cryolite an attractive candidate for soil microbial ecology studies, since bacteria may be visualized even without being fluorescently labeled, obviating the need for genetic modification or staining. Cryolite also has more natural dry-down and wet-up behavior than Nafion (which requires small amounts of surfactants [15% ethylene glycol or 0.1% Tween] to be re-wet after drying; although generally non-toxic [ Blank et al, 1987 ; Man et al, 2017 ], both of these surfactants can cause cell stress [ Hallsworth et al, 2003 ; Nielsen et al, 2016 ] and can be potential sources of nutrient contamination [ Man et al, 2017 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Ethyl alcohol 70% was unable to affect A. lwoffii on epoxy and ceramic surfaces; also it was not effective against B. cepacia and E. coli on ceramic surface and S. maltophilia on epoxy. Alcohols denature proteins and dissolve the lipid membranes (Man et al 2017). On the Acinetobacter haemolyticus P P P P P P P P P P P P P P P P P P Acinetobacter lwoffii P P F P P P P P P P P P P P F P P P Aeromonas hydrophila P P P P P P P P P P P P P P P P P P Aeromonas salmonicida P P P P P P P P P P P P P P P P P P Burkholderia pseudomallei P P P P P P P P P P P P P P P P P P Burkholderia cepacia P P F P P P P P P P F P P P F P P P Burkholderia gladioli P P P P P P P P P P P P P P P P P P Chryseomonas luteola P P P P P P P P P P P P P P P P P P Cronobacter sakazakii P P P P P P P F F P P P P P P P F F Delftia acidovorans P P P P P P P P P P P P P P P P P P Elizabethkingia meningoseptica P P P P P P P P P P P P P P P P P P Enterobacter cloacae P P P P P P P P P P P P P P P P P P Escherichia coli P P F P P P P P P P P P P P F P P P Leclercia adecarboxylata P P P P P P P P P P P P P P P P P P Moraxella catarrhalis P P P P P P P P P P P P P P P P P P Pantoea s p .…”
Section: Discussionmentioning
confidence: 99%
“…The fact that this formulation was the less active than those with less isopropanol but containing 20 to 40% ethanol is an indication that the combination of the two alcohols is more active than using isopropanol alone. Man et al [24] after testing low molecular weight alcohols on bacterial viability concluded that n propyl alcohols were more active followed by isopropanol, n butyl and iso butyl alcohols, and all the precedent compounds were more active that ethanol. In fact alcohols can affect microorganism vitality with two main mechanism [25]; membrane lipid layer solubility and protein alcohol solubility.…”
Section: Discussionmentioning
confidence: 99%